2-Carboxy-1-phenylethanaminium perchlorate - Li, Xiu-Zhi (International Union of Crystallography, 2009)
In the title compound, C(9)H(12)NO(2) (+)·ClO(4) (−), an intramolecular N—H⋯O interaction results in the formation of a six-membered ring having a twisted chair conformation. In the crystal structure, intermolecular O—H⋯O, N—H⋯O and C—H⋯O interactions link the molecules into a network. A weak C—H⋯π interaction is also found.